Case report: VEXAS syndrome: first documented cases in Latin America - Ottati, Carolina; Gervaz, Inés; Yandian, Martín; Boada, Matilde; Vidal-Senmache, Gabriela; Ortiz-Guerra, Percy; Catalán, Ana I.; Kutscher, Patricia; Lopez, Diego; Diaz, Lilian; Grille, Sofia (Frontiers in Hematology, 2025)
IntroductionVEXAS syndrome (Vacuoles, E1 Enzyme, X-linked, Autoinflammatory, Somatic) is a recently identified disorder associated with somatic mutations in the UBA1 gene. Predominantly affecting adult males, it is characterized by a wide range of autoinflammatory symptoms and hematologic abnormalities.MethodsWe present three cases from Latin America, marking the first reported occurrences in this region, to illustrate the clinical variability and diagnostic challenges of VEXAS syndrome.ResultsEach patient exhibited unique clinical presentations, including refractory autoinflammatory symptoms, myelodysplastic syndrome, and bone marrow vacuolization. All cases were confirmed via genetic testing, revealing pathogenic UBA1 mutations alongside other genetic variants commonly linked with myeloid neoplasms.DiscussionThese findings underscore the importance of considering VEXAS syndrome in patients with unexplained inflammatory and hematologic symptoms. The coexistence of UBA1 mutations with other genetic variants suggests a potential overlap with clonal hematopoiesis, complicating the clinical picture. These cases contribute to the understanding of VEXAS syndrome and highlight the need for increased awareness and diagnostic testing in diverse populations to ensure early and accurate diagnosis.